Exploring flubendazole formulations for use in sheep. Pharmacokinetic evaluation of a cyclodextrin-based solution - Ceballos, Laura (2012)
Background: Flubendazole (FLBZ) is a poor water solubility broad-spectrum BZD methylcarbamate anthelmintic compound. Cyclodextrins (CDs) are usually used to increase aqueous solubility of poor hydrosoluble compounds. The comparative in vitro aqueous solubility of FLBZ and other BZD anthelmintics in the presence of hydroxypropyl-β-cyclodextrin (HPβCD) was evaluated in the current work. Additionally, the comparative pharmacokinetic behaviour of FLBZ (and its metabolites) administered by the intraruminal (i.r.) or intraabomasal (i.a.) routes to sheep as either an aqueous CDs-based solution or a conventional carboximethylcellulose (CMC) suspension was assessed. Drug solubility studies involving albendazole, mebendazole, oxfendazole and FLBZ were performed in an aqueous solution (pH 1.2 or 7.4) with or without HPβCD (10%, w/v). The pharmacokinetic study involved two experiments. Experiment 1: In a crossover study, sheep received either a FLBZ-CDs solution (n = 3) or a FLBZ-CMC suspension (n = 3) by the i.r. route (3.8 mg/kg). The treatment Groups were reversed after a 21-days washout period. Experiment 2: sheep (n = 4) were treated by the i.a. route with the FLBZ-CDs solution (3.8 mg/kg). Plasma and abomasal fluid samples were collected between 0 and 72 h post-treatment. Samples were analysed by HPLC. Results: Improvement of FLBZ aqueous solubility due to CDs resulted markedly higher than that observed for mebendazole and albendazole. However, oppositely to what was expected, the absorption-related pharmacokinetic parameters did not show any marked formulation-dependant effect. After the i.a. administration of FLBZ, the AUC and the Tmax of the parent compound were significantly (P < 0.05) reduced, which is consistent with ruminal bypass. Conclusion: The administration of FLBZ as a CDs-based solution, does not seem to achieve great practical relevance for parasite control in sheep.